Aluminum tolerance and micronutrient accumulation in cereal species contrasting in iron efficiency. (9th May 2017) - Bityutskii, Nikolai; Davydovskaya, Helena; Yakkonen, Kirill
ABSTRACT: Aluminum (Al) negatively interferes with the uptake or transport of different nutrients. The aim of our work was to compare the Al tolerance and micronutrient accumulation: iron (Fe), zinc (Zn) and manganese (Mn), in cereal species (winter wheat, spring wheat, winter rye, oats and barley) contrasting in Fe efficiency. Our previous screening in a calcareous soil showed that oats and barley were more Fe-efficient than spring wheat, winter wheat or winter rye. In Al stress conditions, both oats and barley exhibited more effectiveness in Fe acquisition and translocation from root to shoot in comparison to winter wheat, spring wheat and winter rye. Also, oats and barley responded to Al toxicity by less Al-retarded shoot biomass than other cereal species. A combination of tolerance mechanisms appears to have great importance for Al tolerance including mechanisms underlying Fe efficiency in cereal seedlings.